2014
DOI: 10.1109/tits.2013.2286271
|View full text |Cite
|
Sign up to set email alerts
|

Valuating Surface Surveillance Technology for Collaborative Multiple-Spot Control of Airport Departure Operations

Abstract: Airport departure operations are a source of airline delays and passenger frustration. Excessive surface traffic is a cause of increased controller and pilot workload. It is also a source of increased emissions and delays, and it does not yield improved runway throughput. Leveraging the extensive past research on airport departure management, this paper explores the environmental and safety benefits that improved surveillance technologies can bring in the context of gate-or spot-release strategies. This paper … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Indeed, it was found that a rate-based control strategy is much better accepted by human operators than a pure threshold strategy. Generalized versions of pushback control policies, based on fullstate feedback using surface surveillance, have also been considered for surface traffic management [13,14]. Recently, a refined Pushback Rate Control strategy has been developed, which uses the transient analysis of D(t)/E k (t)/1 queuing systems to determine the optimal rate of pushbacks in a given time period, based on the operating environment, the number of aircraft taxiing out, and the length of the departure runway queue [84].…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, it was found that a rate-based control strategy is much better accepted by human operators than a pure threshold strategy. Generalized versions of pushback control policies, based on fullstate feedback using surface surveillance, have also been considered for surface traffic management [13,14]. Recently, a refined Pushback Rate Control strategy has been developed, which uses the transient analysis of D(t)/E k (t)/1 queuing systems to determine the optimal rate of pushbacks in a given time period, based on the operating environment, the number of aircraft taxiing out, and the length of the departure runway queue [84].…”
Section: Methodsmentioning
confidence: 99%
“…The main requirement is to design a layered security structure in such manner that one layer compensates the limitations of another, and to discover the mechanisms that produce mutual reinforcement; the layers providing greater protection together compared to the sum of their individual effects [78]. For example: a) Efficiency of surveillance can be elevated via camera networking and their synchronization for tracking persons of interest, as well as integration of intelligent mechanisms [13], [20]; b) Performance of authentication can be improved via some preliminary traveler identification or recognition [50], and meta-recognition [72]; c) Performance of traveler risk assessment can be improved via a distributed pre-check mechanism [19], [25], [80]; d) Risks of attack can be mitigated via a specific space configuration and a topology of the queuing lines [53].…”
Section: Accepted Manuscriptmentioning
confidence: 99%